Approaches to Ensuring the Reliability of Information in Open Online Encyclopedias. Ruwiki Encyclopedia Experience - Dmitry Rozhkov (Современные информационные технологии и IT-образование)
The article focuses on approaches to ensuring the reliability of information in open online encyclopedias using the example of the Russian Internet encyclopedia Ruwiki. In an information society where the volume of information is constantly growing, it becomes important to ensure its reliability without compromising openness and freedom of expression. The online encyclopedia Ruwiki, based on Wikipedia, is distinguished by enhanced measures to ensure the accuracy of the content. Unlike Wikipedia, which relies on anonymous authors and verifiability through authoritative sources, Ruwiki undergoes rigorous editorial review and peer review of its content, making the encyclopedia a trusted resource, especially in demand for educational purposes such as preparing students for state exams.